Los estados financieros y su relación con las herramientas de gestión del Gobierno Regional de Loreto, durante el año 2021 - Noriega Olortegui, Aníbal Luis (2022)
The accounting unit is linked to the function of taking measures for budget and budget control, based on a sound regulatory framework to ensure that expenses are spent in accordance with existing rules and regulations, construction of a planning system , analysis of financial statements and financial statements. In this sense, the objective of the work is to determine the relationship between the financial statements and the management tools in the Regional Government of Loreto, during the year 2021, for this, a quantitative investigation was carried out, of a non-experimental nature and of a correlational design. The results allowed us to conclude that there is a positive relationship between the financial statements and the management tools of the Regional Government of Loreto, during the period 2021.